SUR UNE CLASSE DES METHODES EFFICACE POUR L'OPTIMISATION SANS CONTRAINTE - Fouad BEDDIAR (My University, 2023)
This thesis presents an in-depth study of a class of hybrid conjugate gradient me- thods for unconstrained optimization. These methods combine two distinct approaches to effectively solve numerical optimization problems. The analysis provides detailed in- sights into the characteristics, properties, and convergence behavior of these methods in different situations. Furthermore, the numerical results demonstrate the effectiveness of the hybrid approach in terms of convergence and solution accuracy, showcasing significant improvements compared to the base methods. ------------------------------------------------------------------------------------------- تقدم هذه الأطروحة دراسة متعمقة لفئة من طرق التدرج المترافق الهجين لتحسين غير مقيد. تجمع هذه الطرق بين نهجين متميزين لحل مشاكل التحسين الرقمي بكفاءة. يفصل التحليل خصائص وسلوك التقارب لهذه الأساليب في المواقف المختلفة. علاوة على ذلك ، أظهرت النتائج العددية كفاءة النهج الهجين من حيث التقارب ودقة الحل ، مع تحسن كبير مقارنة بالطرق الأساسية. ------------------------------------------------------------------------------------------ Ce mémoire présente une étude approfondie d'une classe de méthodes hybrides du gradient conjugué pour l'optimisation sans contrainte. Ces méthodes combinent deux approches distinctes pour résoudre efficacement les problèmes d'optimisation numérique. L'analyse détaille les caractéristiques, les propriétés et le comportement de convergence de ces méthodes dans différentes situations. De plus, les résultats numériques démontrent l'efficacité de l'approche hybride en termes de convergence et de précision de la solution, avec une amélioration significative par rapport aux méthodes de base.